Association of psycho-wellness with various blood types in young medical students - Yadav, Anuradha; Sankhla, Manisha; Gaur, Kusum Lata; Gupta, I. D. (International Journal of Research in Medical Sciences, 2017)
Background: There are many stressors that affect student’s mental health. Many evidences indicate that individuals of different blood group have different response to same stressor, suggesting that the genetics of blood type also appear to alter susceptibility to develop neuropsychiatric disease. This study aimed to find out association of blood group with depression so early detection of depression and stress by blood types helps to reduce the overall burden of illness of young students thus improve their academic performance and social life. Methods: A cross-sectional study was carried out on 226 medical students. They are interrogated as per MMS scale to assess the psycho-wellbeing of students. ABO and Rh blood groups were determined by Anti sera A, Anti sera B and Anti sera D. Data were analysed with Primer version 6 and Chi-square. Results: In the present study it was observed that majority of students belong to blood group B (39.38%), followed by blood group ’O’ (27.88%), ’A’ (27.66%) and ’AB’ (7.08%) respectively. Blood type A was more in red zone and more prone to PTSD (post traumatic syndrome disorders). Whereas blood type B was more prone to suicidal tendency. Proportion of psychomorbidity was found more in Rh+ than Rh (28.16% verse 15%). But these variations were statistically insignificant. Conclusions: Blood type ’A’ and ’Rh+’ were more prone to psycho morbidity and ‘B’ for suicidal tendency, while ’O’ had least suicidal tendency but this variation was not found significant. So it can be concluded that there is no association between blood type and psycho wellness of individual.